Impacts of various high beam headlight intensities on driver visibility and road safety - Prasetijo, Joewono; Mohd Jawi, Z.; Mustafa, M. A.; Zadie, Z.; Majid, H. A.; Roslan, M. H.; Baba, I.; Zulkifli, A. F. H. (Journal of the Society of Automotive Engineers Malaysia, 2018)
Based on several studies, driving above certain speed at night while using low beam headlights has been found to result in insufficient visibility to respond to road hazards. Luckily, vehicle headlight technology has advanced so much and the system is commercially available in many parts of the world. However, the technical development for optimal photometric performance raises a few questions. The use of high beam headlight system creates a glare to drivers of oncoming and preceding vehicles (because of both oncoming headlights and preceding taillights), to the extent that it has become necessary to determine the need to put a limit on the luminous intensity of high-beam headlights. This study shall therefore summarize and investigate visual performance that allows for evaluation of the potential benefits of increased luminous intensity by considering glare rating related to safety. Two different car models; the Proton Prevé and the Perodua Myvi were used in the experiments. The results showed that the highest average illuminance [lux] for single vehicle was 17.5, 7.5, 5.0 and 1.0 for the distances of 30m, 60m, 120m and 150m. However, the average illuminance based on total number of vehicles was 1.0, 0.5, 0.0 and 0.0 at distances of 30m, 60m, 120m and 150m, which were considered below maximum recommended safety level (max. 9.0 – 11.0 lux). The current average vehicle high-beam headlight control was found at the level of acceptable glare control (glare to oncoming and preceding drivers) and below the maximum level of illuminance rate with the normal speed of 40 km/h.